Approaches to Personalizing the Learning Process in Teaching English with the Help of Artificial Intelligence - Hurskaya, Volha (Академічні візії, 2023)
The article analyzes the essence and peculiarities of personalized learning. It was proved that such learning refers to an educational approach that adapts the educational process to students' individual needs, interests, and skills. The article aims to analyze the personalization of the educational process in teaching the English language, focusing on using artificial intelligence. The tasks of the article concern the interpretation of the notion of personalization, the comparative analysis of personalized learning and traditional learning, the description of instruments for personalization of the educational process of teaching the English language, and the development of the plan of personalized lessons. During the investigation, the theoretical research methods were used. They included a literature review, analysis, synthesis, and comparative analysis. The findings showed that teaching foreign languages with a personalized approach has several advantages. At the same time, the comparative analysis demonstrated that personalized teaching of the English language is characterized by the consideration of the individual learning style of a student, the use of educational materials which are developed according to interests, level of knowledge, and educational purposes of students; the use of feedback; the application of motivation instruments; the implementation of student-oriented approach; and the continuous assessment. In the research, we distinguished the principles of personalization in teaching the English language from those of artificial intelligence. These principles were oriented towards adaptability, individualization, and interactivity. Based on these findings, we outlined the strategies that ensure the educational process's efficiency. Also, specific applications and platforms were described that are used for personalized teaching of the English language using artificial intelligence algorithms to adjust the educational materials to students' individual needs. The schematic plan for personalized English language lessons was developed, and the practical recommendations for enhancement of its efficiency were presented.